Qualidade da água de abastecimento e aspectos sociais e comportamentais de seus consumidores no município de Mossoró/RN - Silva, Manoel Marcelino da (Universidade Federal Rural do Semi-Árido, 2017)
Mossoró is located in the state of Rio Grande do Norte, and is located 285 km from Natal, the state capital. Has an area of 2,110.21 km2 and a population of 259,815 habitants. The reality of Mossoró is similar to that of others in the semi-arid region of the Northeast, characterized by long periods of drought and short rainy seasons, so the management of water resources requires optimization in order to meet the needs of the region. Population growth associated with water use levels shows excessive consumption, waste and contamination, generating public health problems, since it directly affects their quality. The questions of potability of water are governed in the country by portaria 2.914 / 2011 / MS. In this perspective, a study of the physical-chemical and microbiological parameters was carried out with samples of the water distributed in the town, originating from the water receiver of the distribution network and the water collector of the residences, and to verify the population's perceptions about knowledge, water use and waste, and about hygiene practices in public health, 385 questionnaires were applied. Regarding the physical parameters, the color and turbidity presented higher results in the collectors of the residences surveyed, indicating the lack of maintenance of these. The chemical analyzes of pH, chlorides and alkalinity did not present major alterations between the studied zones, whereas the hardness and nitrate analyzes were greater in places where there is a deficiency in the sanitation or where there was a greater chance of contamination of the water, such as sewage and garbage. For the microbiological parameters studied, the presence of bacteria of the coliforms group was observed in all points in at least one of the collections, being the greater contamination in the receptors, justified by the lack of maintenance and probably by the lack of prevention in the fence of these collectors, Allowing the access of rodents, insects and other microorganism carriers. Concerning the social aspects and the behavior about available water resources, the population of Mossoró surveyed was mostly in the age range between 18-25 years of age, female, with education at the middle level and family income higher than a salary minimum. The research revealed that the availability of water in the residences is frequent, and most of them have water collectors and are aware of the need to clean these collectors, and that the respondents are not aware of water quality parameters and most do not believe in your quality, but 33,8% of respondents use it to drink. It was also identified that the participant population produces waste and presents awareness about hygiene and health, despite high rates of waterborne diseases
Quality of supply water and social and behavioral aspects of its consumers in Mossoró/RN
Keywords: Qualidade da água; Consumo de água; Desperdício; Saúde pública; Water quality; Water consumption; Waste; Public health; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE